Assessment of essential elements in the wild Beluga Sturgeon (Huso huso) caviar from Caspian Sea - Seyed Vali Hosseini; Seyedeh Fatemeh Monsef Rad; Hamed Kolangi Miandare; Mohamad Harsij; Saeed Sharbaty (International Journal of Aquatic Biology, 2014)
In this study, the concentration of Calcium (Ca), Cobalt (Co), Chromium (Cr), Copper (Cu), Iron (Fe), Potassium (K), Magnesium (Mg), Manganese (Mn), Selenium (Se) and Zinc (Zn) as essential metals, were determined in caviar of wild beluga sturgeon caught from the Caspian Sea in March 2012. Potassium (4885.51± 17.81 µg g-1) and Magnesium (346.61± 6.6 µg g-1) had the highest concentration and Cobalt and Manganese levels were less than 0.01 mg kg-1 wet weight. The mean concentration of Copper and Zinc in the caviar samples were under the permissible limits proposed by the UK’s Ministry of Agriculture, Fisheries and Foods. The caviar maximum allowable daily consumption rate was calculated. However, the health risks from caviar consumption are uncertain because the amount of caviar consumed by heavy users is not known.